Validity and reliability fatigue severity scale in patients with Systemic Lupus Erythematosus (SLE) in Indonesia - A Rifa’i; Handono Kalim; Kusworini Handono; Cesarius Singgih Wahono (Indonesian Journal of Rheumatology, 2016)
Background: Fatigue is one symptom of Systemic Lupus Erythematosus (SLE), which has an important effect on the quality of life. Fatigue Severity Scale (FSS)is one parameter fatigue symptom in SLE. The purpose of this study was to determine the validity and reliabilitybetween FSS with duration of ilness and disease activity of SLE patients in Indonesia.Methods: FSS performed on 40 patients with SLE. FSS original English version has been converted-translated into Indonesian version by a team of RheumatologyImmunology Medical Faculty of Brawijaya University. Reliability determined by Cronbach’s Alpha values (>0.6). Validity was determined by the value of Corrected Item-Total Correlation which each item was a valid question if below value of Cronbach’s Alpha.Results: The reliability value was determined by Cronbach’s Alpha values (>0.6) in which the SLE patients in this study had a Cronbach’s Alpha value of 0.946. Value of Corrected Item-Total Correlation overall under Cronbach’s Alpha value (range = 0.684-0.859) which indicates that each item was a valid question. There were correlation between the FSS Indonesian version with disease duration (p = 0.000) as well as the value of r = 0.581, with SLEDAI (p = 0.000) with a value of r = 0.833. Conclusion: FSS in Indonesian version has a good reliability and validity and can be used by clinicians andother researchers to assess the condition of fatigue in SLE patients in Indonesia.Keywords: validity, reliability, fatigue, fatigue severity scale, systemic lupus erythematosus